The ethos of the auteur as father of the film craft – on masculinity, creativity and the art of filmmaking - Aharoni Lir, Shlomit; Ayalon, Liat (Creativity Studies, 2022)
Research of the world of cinema often deals with the manner in which movies replicate the social balance of power, creating a symbolic order based on an essentially masculine world-view that puts the man at its center. The price women pay for this phallocentric approach – their persistent objectification in cinema, and the very small number of female screenwriters and directors – has become a much-discussed topic in contemporary research. However, the question of the price paid in the male artistic creation process has yet to receive the attention it deserves. This qualitative study addresses the lacuna in contemporary research, with reference to three metafictional films that focus on male directors, as an auteur for whom cinema is the pivotal center of their being: the Israeli film Peaches and Cream (2019, directed by Gur Bentwich), the Spanish film Pain and Glory (in Spanish: Dolor y gloria, 2019, directed by Pedro Almodóvar), and American film All That Jazz (1979, directed by Bob Fosse). They all are viewed as having an affinity with the ancient Greek comparison of male creativity with female procreativity, which is still reflected in contemporary studies. The films paint a picture of the male creative process shadowed by a sense of danger and loss of self. All three expose the feelings of anxiety inherent in film directors’ work, and the possible resultant breakdown, not only in an emotional sense but in a real, potentially fatal physical or medical sense as well. In all three movies, the director conceives of his ability to restore his sense of inner wholeness and male identity in a manner that contradicts the conventional balance of power, while customary power-relations are revealed as another road to loss of identity and sense of self. Each of the films ties the director’s ability to renew his sense of personal wholeness to developing a relationship with his surroundings, facilitated by audience appreciation, critical praise, or empathy from those close to him – all of which reinforce his feeling of belonging and significance. Without these aspects, the “absolute artist”, whose life revolves around his art, is shown to be at death’s door, whether symbolically or in reality.